Pengaruh Model Pembelajaran Treffinger Berorientasi Kearifan Lokal Berbantuan Tugas Berjenjang Terhadap Self Efficacy Dan Kompetensi Strategis Matematika Siswa Sekolah Menengah Pertama (SMP) - Ayuningsih, Ni Putu Meina; Dwijayani, Ni Made (Kreano, Jurnal Matematika Kreatif-Inovatif, 2019)
This study aims to find out whether: (1) self efficacy mathematics of students who are taught by the learning model of Treffinger oriented local wisdom with better-tiered assignment or not from self efficacy of students receiving conventional learning, (2) students' mathematics student competence taught by model Lessons are used to perform better or better tasks from students receiving conventional learning, (3) there is some self-efficacy and simultaneous mathematical strategies between students who are taught by Treffinger-aided learning model with tiered assignments conventional learning. This research type is quasi experiment with posttest only control group design. Data in this research is self efficacy mathematics used by using questionnaire and data required by student. The data obtained were analyzed descriptively on the basis of t-test 1 for hypothesis 1 and hypothesis 2, and MANOVA test for hypothesis 3. Characteristics of the teaching-oriented model of Treffinger oriented local wisdom with the help of this tiered function are: (1) student involvement in the problem and they as participants active in problem solving, (2) the science of cognitive dimension and student affectivity to seek the direction of problem solving provided, (3) the students do group analysis to explore ideas, and (4) the students use the acquired understanding to solve other related problems with everyday life. In addition, by delivering advice sourced from Bali's reliable local wisdom and making the process more enjoyable. Given tiered tasks in learning mathematics such as practice questions that can be done effectively. Through the learning model oriented Treffinger local wisdom assisted by this tiered task is expected students are able to solve problems in a way with their own. The process of thinking to discuss mathematical problems and will foster confidence in students to solve problems related to other terms for the next. To complete the problem of tiered training well, also required good students also.